A review of the potential of induced pluripotent stem cell-derived exosome as a novel treatment for male infertility - Sojoudi, Kiana; Azizi, Hossein; Skutella, Thomas (Biotechnology & genetic engineering reviews, 2024)
Exosomes are a subset of Extracellular vesicles (EVs) released by most cells in the body and can play a significant role in the intercellular connection. Researchers today claim that exosomes secreted by induced pluripotent stem cells (iPSCs) alone can play the same role as direct cell transplantation and, unlike iPSCs, do not lead to tumorigenesis. As a result, iPSC-derived exosomes (iPSC-Exos) have many applications in cell-free treatments and therapeutic effects on various diseases. Male infertility due to a defect or deficiency of spermatogonia to maintain spermatogenesis is one of the diseases that iPSC-Exos seems to be a new way to cure. However, the studies on the effect of iPSC-Exos on male infertility are very limited. In this review, we intend to provide a broader perspective on understanding the mechanisms of iPSC-Exos on spermatogenesis by collecting and reviewing some of the research conducted in this field.
Online veröffentlicht: 23 März 2023
Gesehen am 10.10.2024